Regional Comparative Analysis of Family Catastrophic Health Expenditure in Pakistan - Saif Ullah; Dr. Abdur Rehman; Dr. Muhammad Niamat Ullah Khan Babar; Dr. Farman Ullah Khan; Muhammad Waqar; Shehla Mazhar; Bushra Zaman; Saima Munir; Muhammad Eshan Elahi (Indus Journal of Social Sciences, 2025)
The amount of money Pakistani families spend on medical care is examined in this paper making use of PSLM data for 2018–19. It looks into the elements and factors that affect how much money families spend on various illnesses. Numerous factors, such as the type of disease, the number of people living in different provinces, the location (rural or urban) and age of the family heads affect the cost of a family’s catastrophic expenditure. According to the estimation results, it can be concluded that in light of all factors have a positive influence on policy recommendations for health expenditure. Furthermore, any finding could have a broad impact on health expenditure of Pakistan. Each of these elements has a distinct impact on how the government determines what amount of funding to allocate to the health sector. The regression was conducted using regression analysis and the ordinary least squares (OLS) method. This method and technique are used in specific situations when the dependent variable in a model is quantitative. Estimates and results will be used to develop the policy and find solutions for every issue that can be attributed to the variables and household health spending.